2011
DOI: 10.1002/jbmr.1466
|View full text |Cite
|
Sign up to set email alerts
|

The association between fracture and obesity is site-dependent: A population-based study in postmenopausal women

Abstract: The association between obesity and fracture is controversial. We investigated the relationship between body mass index (BMI) and fracture at different skeletal sites in women aged !50 years using data from the Sistema d' Informació per al Desenvolupament de la Investigació en Atenció Primària (SIDIAP) database. SIDIAP contains the computerized medical records of >3400 general practitioners in Catalonia (northeastern Spain), with information on a representative 80% of the population (>5 million people). In 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
216
4
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(251 citation statements)
references
References 25 publications
15
216
4
16
Order By: Relevance
“…Several studies have demonstrated that the relationship between BMI and fracture is site-specific (8,11,12,14,16,21,22). While obesity is protective against hip fracture in women, it is associated with higher risk of fractures at some other sites.…”
Section: Site Of Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the relationship between BMI and fracture is site-specific (8,11,12,14,16,21,22). While obesity is protective against hip fracture in women, it is associated with higher risk of fractures at some other sites.…”
Section: Site Of Fracturementioning
confidence: 99%
“…Subsequently, other investigators have studied the impact of obesity on bone mass and the risk of fracture (9)(10)(11)(12)(13)(14). The present review focuses on the epidemiology, risk factors, diagnosis, and management of fractures in obese postmenopausal women and older men.…”
mentioning
confidence: 99%
“…A number of previous studies have revealed that obesity stimulates bone formation by inhibiting apoptosis. A recent study demonstrated that high BMI prevents normal bone fracture and osteoporotic fracture in various age groups and genders (7). By contrast, it has also been reported that osteoporosis occurs in obese individuals (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, fracture risk in obesity is not lower at all skeletal sites; the risk of some non-spine fractures including proximal humerus (RR 1.28), upper leg (OR 1.7) and ankle fracture (OR 1.5) is higher [4,5]. A large number of low-trauma fractures occur in overweight and obese men and women, and the prevalence of low-trauma fractures is similar in obese and non-obese women [6].…”
Section: Obesity Fracture and Bmdmentioning
confidence: 99%